A Rare Case of Severe Dilated Cardiomyopathy in Early Infancy - Schwendt, Meike; Kroll, Johannes; Fleck, Thilo; Stiller, Brigitte (The Thoracic and Cardiovascular Surgeon Reports, 2021)
We report the case of a 3-month-old girl presenting with end-stage dilated cardiomyopathy and therapy-resistant cardiogenic shock. A left ventricular assist device (LVAD) Berlin Heart EXCOR was implanted, her organs recovered, and she was listed for heart transplantation. Two months later, while still on the LVAD, she was diagnosed with the rare genetic Alström syndrome. Weaning was no option, and she underwent successful heart transplantation at the age of 9 months. The follow-up 15 months later revealed an uneventful transplant course in a child with Alström syndrome.
Keywords: cardiomyopathy; Alström syndrome; Berlin Heart EXCOR; heart transplantation